Plasma pharmacokinetics of once- versus twice-daily lamivudine and abacavir: simplification of combination treatment in HIV-1-infected children (PENTA-13). - Bergshoeff, A; Burger, D; Verweij, C; Farrelly, L; Flynn, J; Le Prevost, M; Walker, S; Novelli, V; Lyall, H; Khoo, S; Gibb, D (2005)
BACKGROUND: There are few data on plasma and intracellular pharmacokinetics (PK) of once-daily (q24h) nucleoside analogues in HIV-infected children. METHODS: Children aged 2-13 years receiving combination treatment containing lamivudine (3TC) (4 mg/kg) and/or abacavir (ABC) (8 mg/kg) twice daily (q12h) were included in this single-arm, open-label, crossover study. Intensive plasma PK sampling was performed at steady state, after which children switched to q24h dosing and PK sampling was repeated 4 weeks later. Daily area under the curve (AUC0-24) and peak level (Cmax) of q24h and q12h regimens were compared by geometric mean ratios (GMRs) with 90% confidence intervals (CIs). Children were followed for 24 weeks to evaluate safety and virological response. RESULTS: 24 children were enrolled, of whom 20 [median age (range) 5.6 (2.1-12.8) years] had evaluable PK data for 3TC (n=19) and/or ABC (n=14). GMRs of 3TC and ABC AUC0-24 and Cmax q24h versus q12h significantly exceeded 1.0. GMRs were not significantly different between children aged 2-6 versus 6-13 years old (P>0.08). Of note, 3TC Cmax values for both q12h and q24h were significantly lower in children aged 2-6 versus 6-13 years old. No child discontinued due to adverse events. At baseline, 16 out of 20 children had a viral load <100 copies/ml compared with 17 out of 19 at week 24. CONCLUSION: AUC0-24 and Cmax of both 3TC and ABC q24h were not inferior to q12h dosing in children. Insufficient results were obtained concerning intracellular levels of the active triphosphate moieties of both agents. Virological data did not indicate a marked difference in antiviral activity between q12h and q24h regimens.